Framework of One Piece Flag Symbol That Used by Demonstration in Indonesia, Nepal, and Philippines - Febri Azwar Ilham; Yusri Bayu Aditya; Euis Meinawati (Universitas Islam Negeri Palopo, 2026)
This study examines the use of the One Piece Jolly Roger flag as a symbolic resource in youth-led protest movements in Indonesia, Nepal, and the Philippines. Employing a descriptive qualitative approach, the research applies Critical Discourse Analysis, drawing on Fairclough’s discourse framework and van Dijk’s socio-cognitive perspective, alongside visual–semiotic analysis. The data consist of three representative protest images—one from each country—supported by related media texts from international news coverage. The findings reveal that although the same pop-culture symbol circulates transnationally, its meanings are locally rearticulated: the flag functions as satirical political critique in Indonesia, as confrontational resistance in Nepal, and as a tool of digitally mediated mobilization and accountability in the Philippines. These variations demonstrate how youth activists strategically adapt global popular culture to express localized political grievances while maintaining a shared discourse of resistance. This study contributes to discussions on youth activism and visual political communication by highlighting how fictional symbols can operate as powerful discursive instruments in contemporary protest movements.